2018
DOI: 10.1038/s41598-018-29186-z
|View full text |Cite
|
Sign up to set email alerts
|

Inter-individual differences in contamination profiles as tracer of social group association in stranded sperm whales

Abstract: Ecological and physiological factors lead to different contamination patterns in individual marine mammals. The objective of the present study was to assess whether variations in contamination profiles are indicative of social structures of young male sperm whales as they might reflect a variation in feeding preferences and/or in utilized feeding grounds. We used a total of 61 variables associated with organic compounds and trace element concentrations measured in muscle, liver, kidney and blubber gained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Autenrieth et al’s [ 15 ] genetic analysis suggested that the 27 male sperm whales that stranded together in the North Sea were not maternally related individuals but instead included assemblages of individuals from different natal geographic regions. Schnitzler et al [ 16 ] also reported evidence for at least two cohorts with different origins among 24 of these males based on contaminant and genetic analyses. Considering the long calving intervals of individual females (every 4~6 years) [ 13 , 17 ] and the size of female family units (~10; [ 6 ]), it would be almost impossible to form an all-male group consisting of more than very few related males of approximately the same age.…”
Section: Introductionmentioning
confidence: 99%
“…Autenrieth et al’s [ 15 ] genetic analysis suggested that the 27 male sperm whales that stranded together in the North Sea were not maternally related individuals but instead included assemblages of individuals from different natal geographic regions. Schnitzler et al [ 16 ] also reported evidence for at least two cohorts with different origins among 24 of these males based on contaminant and genetic analyses. Considering the long calving intervals of individual females (every 4~6 years) [ 13 , 17 ] and the size of female family units (~10; [ 6 ]), it would be almost impossible to form an all-male group consisting of more than very few related males of approximately the same age.…”
Section: Introductionmentioning
confidence: 99%
“…Levels of a range of contaminants were determined, but were not considered to be of significance in terms of causality of the mortality event (details in [ 60 ]). Data on contaminant profiles together with genetic data gave evidence for at least two cohorts among the stranded sperm whales with different origins; one from the Canary Islands and one from the northern part of the Atlantic [ 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Levels of a range of contaminants were determined, but were not considered to be of significance in terms of causality of the mortality event (details in [ 60 ]). Data on contaminant profiles together with genetic data gave evidence for at least two cohorts among the stranded sperm whales with different origins; one from the Canary Islands and one from the northern part of the Atlantic [ 59 , 60 ]. The genetic diversity was comparable to the genetic diversity in sperm whales from the entire Atlantic Ocean and males did not comprise maternally related individuals within this stranding event, but assemblages of individuals from different geographic regions [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations